THE ROLE OF GOVERNMENT POLICIES IN ENHANCING THE PERFORMANCE OF THE SAUDI FINANCIAL MARKET WITHIN THE FRAMEWORK OF VISION 2030 - Djihed BOUMANKAR; Aboubaker KHOUALED; Khayreddine BOUZERB; Abderrahmen GUEROUI (Annals of the University of Oradea: Economic Science)
Financial markets are the backbone of the economy for many countries worldwide due to their importance in achieving balance within the overall financial system. They do this through various roles and tasks, such as hedging operations and managing different investments in financial instruments like stocks and bonds. This makes the management policies of financial markets significantly impact the financial environment specifically, and the global economy in general. The primary objective of this study is to clarify the role played by various government policies and procedures in improving the performance of financial markets and enhancing their contribution to the local economies of emerging countries, with a focus on the case of the Kingdom of Saudi Arabia. Equally important is the study’s aim to draw attention to ways to improve the performance of financial markets and provide an initial study on this topic, which is relatively new for Arab countries, where previous local studies remain scarce. On another level, diagnosing the governmental policies adopted in managing financial markets and revealing their various advantages and the challenges they face is highly beneficial for developing future strategies to advance these markets and enhance their competitiveness. To achieve this objective, an exploratory study was conducted based on various secondary sources, data, and reports issued by the Saudi Tadawul market. The study concluded that the different government measures adopted by the Kingdom of Saudi Arabia as part of its vision during the period 2010-2030 had a positive impact on the Saudi financial market, which has notably improved despite the economic conditions and geopolitical crises the world is currently witnessing.